Longevity and fecundity of laboratoryreared Liotryphon caudatus an ectoparasitoid of codling moth - Davis, V.A.; Sandanayaka, W.R.M.; Charles, J.G. (New Zealand Plant Protection, 2016)
Liotryphon caudatus was introduced into New Zealand to control codling moth (CM; Cydia pomonella) in the early 1900s As part of ongoing research into the biological control of CM a laboratory colony of L caudatus was established from fieldcollected adults reared on diapausing CM larvae The longevity and fecundity of laboratoryreared L caudatus adults were measured at 231C and 16 h photoperiod Longevity in a nonhost environment was measured by holding a newly emerged female and a male in a container with water and food Survival of 18 pairs was monitored daily The food and water in the containers were refreshed regularly The fecundity and the longevity of females were measured by providing five diapausing CM larvae to each of nine mated females (age 710 days) in a similar container with food and water The CM larvae were replaced every 48 hours until the females were dead In the interactions between L caudatus and Mastrus ridens a recently released gregarious ectoparasitoid of codling moth in applegrowing areas where L caudatus has already established